The Yellow Book Learning Method at Al-Hidayat Islamic Boarding School in Batulungguh, Central Lampung - Wangga Adiska; Wahyu Sudrajat (Episteme: Jurnal Kajian Mahasiswa, 2025)
This study aims to explore the implementation of the yellow book learning method at Al-Hidayat Islamic Boarding School in Batulungguh, Bangun Rejo District, Central Lampung. The yellow book is one of the distinctive intellectual traditions within the pesantren environment that plays a significant role in shaping the Islamic understanding of the students (santri). The focus of this research includes the teaching techniques used, the challenges faced, and the obstacles encountered in the yellow book learning process. The purpose of this study is to examine the methods of learning the yellow book, along with the challenges and obstacles at Al-Hidayat Islamic Boarding School in Batulungguh, Central Lampung. The research method used is a qualitative approach with a descriptive design. data was collected through observations, in-depth interviews with the caretakers of Al-Hidayat pesantren and its students, as well as document analysis related to the yellow book learning methods, the challenges, and the obstacles,The results of the study reveal that classical methods such as sorogan and bandongan remain the main techniques implemented at Al-Hidayat, complemented by a spiritual approach. The learning materials include salaf books or yellow books. The primary obstacles found include the low proficiency in Arabic and nahwu sorof among beginner students, as well as limited access to modern learning materials for some senior students.